The Onset and Solidification Path of a Basaltic Melt by in situ Differential Scanning Calorimetry (DSC) and ex situ Investigations - Giuliani, Letizia; Iezzi, Gianluca; Hippeli, Tyler; Davis, Mark; Elbrecht, Aubrey; Vetere, Francesco; Nazzari, Manuela; Mollo, Silvio (Frontiers in Earth Science, 2020)
The in-situ differential scanning calorimetry (DSC) technique has been applied to investigate the solidification paths of a basaltic liquid. The starting glass was heated up to 1300 °C, kept at this superliquidus temperature for 2 h and cooled at rates (∆T/∆t) of 7, 60, 180, 1000, and 1800 °C/h, down to 800 and 600 °C. Glass transition temperature (Tg), crystallization temperature (Tx_HR) and melting temperature (Tm) were measured by in-situ DSC spectra on heating. Tx measured along the cooling paths (Tx_CR) shows exothermic peaks that change from a single symmetric shape (7 and 60 °C/h) to multi-component patterns (180, 1000 and 1800 °C/h). The recovered products characterized by FE-SEM and EPMA-WDS show a phase assemblage of spinel (sp), clinopyroxene (cpx), melilite (mel), plagioclase (plg), and glass. Moreover, crystal size distributions (CSDs) and growth rates (Gmax and GCSD) were also determined. The crystal content slightly increases from 7 to 1800 °C/h. Faceted sp are present in all the run products with an amount always < 2 area%. Cpx increases from 7 to 1800 °C/h, changing its texture from almost faceted to dendritic between 60 and 180 °C/h. The area% of mel follows an asymmetric Gaussian trend, while plg nucleates only at 7 °C/h with a content < 2 area%. The coupling of DSC and SEM outcomes indicate that sp nucleate first, followed by cpx and mel (and/or plg). The increment of ∆T/∆t causes an increase of the CSD slope (m) and crystal population density per size (n0), as well as a decrease of the crystal size, for both cpx and sp. The log-linear CSD segments with different slopes at 7 and 60 °C/h suggest multiple nucleation events and crystal growth by coarsening. Gmax and GCSD for cpx and sp directly measured on the actual crystallization time by DSC spectra, both increase with the increasing of ∆T/∆t. The onset temperature of crystallization (Txi) decreases as ∆T/∆t increases, following an exponential trend that defines the uppermost portion of a time-transformation-temperature (TTT)-like curve. This analytical model allows us to quantitatively model the kinetic crystallization paths of dry basalts.